Regulation of the structure formation of ceramic masses of the system multimineral clay– kaolin-feldspar raw materials - Оксамит, Тетяна Валеріївна (Eastern-European Journal of Enterprise Technologies, 2014)
Polymineral clay raw materials with absent sintering interval was selected as the main raw material for the synthesis of ceramic masses, production of ceramic clinker for various purposes using the plastic extrusion method. Kaolin and pegmatite from the Khmelivskyi deposit that may act as fluxing agents were selected as kaolinite-feldspar raw materials. Methods of directed structure formation regulation of ceramic masses based on polymineral clay raw materials using kaolinite-natural feldspar raw materials were investigated. Using mathematical planning, mathematical models of interaction and influence of various technological factors on the properties of experimental masses were developed. Using the correlation analysis method, the relationships in the system polymineral clay-kaolinite-natural feldspar raw materials were examined. Based on the ceramic mass 9 and 11 of the system polymineral clay-montmorillonite-substandard kaolin-pegmatite of the Khmelivskyi deposit, possibility to produce ceramic clinker by optimizing the chemical-mineralogical composition, and masses with a wide sintering interval was shown.